Molecular plant taxonomy: methods and protocols - Besse, Pascale, Ed (Methods in molecular biology, 2014)
Plant taxonomy is an ancient discipline facing new challenges with the current availability of a vast array of molecular approaches which allow reliable genealogy-based classifications. Although the primary focus of plant taxonomy is on the delimitation of species, molecular approaches also provide a better understanding of evolutionary processes, a particularly important issue for some taxonomic complex groups. 'Molecular Plant Taxonomy: Methods and Protocols" describes laboratory protocols based on the use of nucleic acids and chromosomes for plant taxonomy, as well as guidelines for phylogenetic analysis of molecular data. Experts in the field also contribute review and application chapters that will encourage the reader to develop an integrative taxonomy approach, combining nucleic acid and cytogenetic data together with other crucial information (taxonomy, morphology, anatomy, ecology, reproductive biology, biogeography, paleobotany), which will help not only to best circumvent species delimitation but also to resolve the evolutionary processes in play. Written in the successful "Methods in Molecular Biology" series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Molecular Plant Taxonomy: Methods and Protocols seeks toprovide conceptual as well as technical guidelines to plant taxonomists and geneticists.--